The nature, objectives and problems of the elementary on-campus student teaching program, Institute of Education, Far Eastern University - Peralta, Nelly Quinones 1943- ([Quezon City s.n.], 1967)
This study presents the nature, the objectives, and the problems of the elementary on-campus student teaching program of the Institute of Education, Far Eastern University in an attempt to identify the problems of the student teachers on-campus and those involved in the program as a whole for the second semester 1966-1967.
Thesis (M.Ed.)--University of the Philippines
Keywords: Student teachers; Elementary teachers,Training of; Interns (Education).